Biphenyl Based Non-symmetrical Bent-Core Mesogens Containing a Chiral Moiety and an Olefinic End Group - Ocak, Hale; Bilgin-Eran, Belkiz (TAYLOR & FRANCIS LTD, 2015)
New nonsymmetrical bent-core compounds consisting of a biphenyl-3,4 '-diol central unit, a chiral terminal chain and an olefinic end group at the other terminus have been synthesized and characterized to study the influence of a chiral moiety, the length of terminal alkenyl chain, and the number of aromatic rings in the rod-like wings which are substituted at the 3- and 4-position of central biphenyl core on mesophase properties of bent-core mesogens. The liquid crystalline properties of the compounds were investigated by differential scanning calorimetry, optical polarizing microscopy, and electro-optic methods. Depending on the length of the olefinic chain and the number of aromatic rings in the rod-like wings, the bent-core compounds with a chiral moiety show B-1 type mesophase, polar smectic C phase (SmCP) or nonmesomorphic behavior.
Keywords: chiral moiety; olefinic end group; liquid crystals; rod-like wings; Bent-core mesogens; LIQUID-CRYSTALLINE PHASES; CROSS-COUPLING REACTIONS; MESOMORPHIC PROPERTIES; ACHIRAL MOLECULES; POLAR ORDER; MESOPHASE; BEHAVIOR; SYSTEMS; CHAINS; ACIDS; Chemistry; Crystallography; Materials Science